Resepsi Anggota Komunitas Motoladies Mengenai Stereotip Perempuan Pengendara Moge di Media Online - Lulu Pranidhar; Nani Kurniasari (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2022)
Motorbike riding is still often differentiated in society based on gender, this is denied by many mass media and the Motoladies community. The study aims to find out about the reception of Motoladies community members regarding to the female stereotype in riding big bikes of online media, using Stuart Hall’s Encoding-Decoding theory. The paragim audience reception analysis, with three positions namely Dominant Hegemony, Negotiation, Opposition. Based on the result of the study, six informants enter the position of Dominant Hegemony and one informant in the position of Negotiation. All the informants give big support for changing the stereotype of female in riding big bikes regarding to the mess media in this research.